Actor Relations in Interregional Cooperation Policy Dynamics Case Study: The Banjar Bakula Metropolitan Area Development Program in South Kalimantan Province - Taufik Abrain (Indonesian Association for Public Administration, 2018)
Several studies have shown that the success of interregional cooperation may be influenced by coordination, commitment, participation, variance of cooperation, structure, format of cooperation, and political will. Nevertheless, these factors do not stand alone since actor relations as a determining aspect is capable of driving those factors eﬀectively. This article aims to examine the aspect of actor relations as a contributing factor that determines successful cooperation among regions. This is a qualitative research with the policy of inter-regional cooperation of the Banjarbakula Program, South Kalimantan Province from February 2017 to February 2018, set as its object of study. The result of this study states that the success of inter-regional cooperation is influenced by the relationship of actors in development factors as suggested by previous experts. The actors involved in the inter-regional cooperation examined in this case had become triggers of coordination, commitment, and participation toward success and failure, as well as the eﬀectiveness of regional cooperation policy. Structural obstacles, ego-centric character, minimum budget availability, and non-visionary planning could be overcome as long as actor relations were properly managed.